Bronson M. Cutting papers - Cutting, Bronson M., 1888-1935.
Correspondence, essays, articles, speeches, detective reports, biographical information, legal papers, clippings, scrapbooks, printed matter, photographs, and other papers relating chiefly to Cutting's career as a publisher and to his service as a U.S. senator (1927-1935). His files as a publisher relate to political affairs in New Mexico and his investigations into political corruption in the state; and his files as a U.S. senator pertain to banking, congressional campaigns and an election dispute with Dennis Chavez, veterans' claims cases, and other legislative issues. Correspondents include Harold L. Ickes, Ezra Pound, and Theodore Roosevelt.
Publisher and U.S. senator from New Mexico. Full name: Bronson Murray Cutting.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chavez, Dennis, -- 1888-1962.; Ickes, Harold L. -- 1874-1952 -- Correspondence; Pound, Ezra, -- 1885-1972 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; United States. -- Congress -- Elections; American newspapers -- New Mexico; Banks and banking; Contested elections -- New Mexico; Political corruption -- New Mexico; Veterans -- United States; New Mexico -- Politics and government -- 1848-1950.; United States -- Politics and government -- 1901-1953.; Publishers; Senators, U.S. Congress -- New Mexico